Association of early parent-child separation with depression, social and academic performance in adolescence and early adulthood: a prospective cohort study - Honghua Li; Kai Liu; Junsong Fei; Tongshuang Yuan; Songli Mei (BMC, 2024)
Abstract Objective The present study aimed to investigate the long-term effects of parent-child separation during infancy and early childhood on depression, social relationships including parent-child and peer relationships, and academic performance during adolescence and early adulthood. Methods Data from the China Family Panel Studies (CFPS) were analyzed, which included a sample of 3829 children aged 4-15 years from 25 provinces over a period of 8 years. The study examined the association between early parent-child separation and outcomes related to depression, social and academic performance, comparing outcomes between individuals with and without early separation experiences. A series of subgroup analyses were conducted to further explore these associations. Results Parent-child separation lasting 3 months or longer was found to be associated with moderate to severe levels of depression and impaired social relationships during adolescence and early adulthood, particularly among males, adolescents, urban dwellers, and those with less educated mothers. Children who experienced parent-child separation for 3 months or longer showed a positive correlation between separation duration and depression. Short-term separations under 3 months did not show this association. The duration of separation also had a negative correlation with parent-child and peer relationships, as well as academic performance. Conclusion Early parent-child separation has significant adverse effects on the mental health, social and academic performance of adolescents and early adulthood, especially among males, adolescents, urban residents, and those with lower maternal education. The severity of depression was found to be related to the duration of separation, highlighting the importance of minimizing separation to less than 3 months for children under the age of 3. These findings underscore the critical role of early parental care and the need for targeted interventions for high-risk populations.